Pengaruh Gaya Kepemimpinan Transformasional terhadap Kinerja Karyawan Farina Beauty Clinic Karawang - Nandari Nur Iqnatia; Widya Kumala Dewi; Farida Asya; Linda Purnamasari; Umi Zahro Dewi Utami; Saniyyah Nurul Fadilah; Alma Arizulhaq (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effect of transformational leadership style on employee performance at Farina Beauty Clinic Karawang. The research employed a quantitative explanatory design using simple linear regression analysis. The population consisted of 33 active employees, all of whom were selected as the sample through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed with IBM SPSS. The findings indicate that all research instruments were valid and reliable. The regression analysis produced the equation Ŷ = 7.130 + 0.515X with a coefficient of determination (R²) of 0.635, indicating that transformational leadership explains 63.5% of the variance in employee performance. The t-value of 7.351 with a significance level of 0.000 (<0.05) confirms a positive and significant effect of transformational leadership on employee performance. The novelty of this study lies in directly examining the relationship between the two variables in a beauty clinic setting without incorporating mediating variables, thereby providing new empirical evidence for human resource management in the beauty service industry